2011
DOI: 10.1007/s12393-011-9037-5
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum Frying: An Alternative to Obtain High-Quality Dried Products

Abstract: Vacuum frying is an alternative way to improve the quality of the fried food and could reduce the final oil uptake in the product. The product is heated at low pressure thus decreasing the boiling points of the frying oil and the water in the product. Moreover, the absence of air during vacuum frying may inhibit lipid oxidation and enzymatic browning, and therefore, the color and nutrients of samples can be largely preserved. Many food research projects involving snack food industries therefore attempt to unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 93 publications
(180 reference statements)
1
40
0
2
Order By: Relevance
“…Andres-Bello et al 1 identified three vacuum frying equipment based on size: laboratory, pilot and industrial scale system and in terms of processing requirements: for batch or continuous processes. The authors have accordingly elaborated on three examples of vacuum frying systems.…”
Section: Vacuum Frying Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Andres-Bello et al 1 identified three vacuum frying equipment based on size: laboratory, pilot and industrial scale system and in terms of processing requirements: for batch or continuous processes. The authors have accordingly elaborated on three examples of vacuum frying systems.…”
Section: Vacuum Frying Systemsmentioning
confidence: 99%
“…6 The foremost factors that impact fried products are the frying time-temperature combination of the process; the correct combination is necessary to produce a food product with acceptable physical attributes. 1 Dueik & Bouchon 6 reported that vacuum frying pointedly lowered the final oil content in comparison to atmospheric fried food products and it also significantly reduced the rancidity of the oil used for frying. Most of the benefits from vacuum frying could be attributed to usage of low temperatures (105°C), the minimal exposure to oxygen, which diminishes the adverse effects on the oil quality.…”
Section: Advantages Of Vacuum Fryingmentioning
confidence: 99%
“…Dueik and Bouchon [28] put emphasis on the microstructure, methods to reduce oil uptake, oil quality, bioactive compound degradation, and toxic compound generation. Andres-Bello et al [8] reviewed the vacuum-frying processing for producing highquality fried products, focusing on equipment types, pre-treatments, and vacuum-frying conditions.…”
Section: Introductionmentioning
confidence: 99%
“…When this type of croquette is manufactured at industrial scale, the next processing steps are carried out: (1) stirfrying of some ingredients; (2) mixing of all ingredients with water and boiling for making dough which constitutes the filling of the croquettes; (3) dough cooling with cold air; (4) dough extruding, dividing and forming for achieving the required shape and size of the croquettes; then, (5) coating is applied to the croquettes, first with a batter, and secondly with breadcrumbs; and the croquettes are conveyed to the (6) continuous freezing, and (7) packaging later as precooked frozen croquettes, or they are directly conveyed to packaging and cooling for obtaining precooked refrigerated croquettes. Before consumption, at the foodservice sector (for example the kitchen of the restaurant or canteen), or at the home kitchen, the croquettes are generally deep-fried to create a golden and crunchy outer crust.…”
Section: Introductionmentioning
confidence: 99%